ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) PADA EVALUASI TEMATIK BERMUATAN IPS SISWA KELAS V SDN BADRAN YOGYAKARTA - Uswah, Emma Mar’atul; Wardani, Kristi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study is a qualitative study aimed at describing: 1) how is the suitability of HOTS analysis in the thematic evaluation of social studies containing fifth-grade students at SDN Badran Yogyakarta; 2) how about the quality of evaluation questions, how to make evaluation questions; 3) difficulties encountered in making thematic evaluation questions with social studies according to HOTS criteria; 4) the work done prepares teachers to be able to implement HOTS and is there a re-checking of thematic evaluation questions. Data collection techniques using observation, interviews, and documentation studies. Data analysis techniques used the Huber and Mayer analysis techniques and HOTS analysis instruments to analyze the questions. The results of this study are: 1) HOTS analysis on the thematic evaluation of social studies students in grade V SDN Badran Yogyakarta produced a percentage of 53.75%, 2) the quality of thematic evaluation of social studies is quite good because they are made using various references, adjusted KD and students' abilities, 3 ) the questions are made based on the criteria of questions, based on KD, KKO, students 'abilities, and checked again 4) the teacher's difficulty is extensive and difficult social studies material, the ability to understand HOTS and make good items according to students' abilities. 5) the effort made is to bring in the speakers, involve the teacher in education and training, fulfill K13 pre-education facilities in stages. 5) there is a re-checking of questions in the form of a teacher, fellow teacher, TU, and school principal examinations. Breaking up the items is not done because it takes time, the school does not have a special team to study the evaluation questions.